PENGUATAN NILAI-NILAI KEARIFAN LOKAL DALAM PEMBELAJARAN IPA PADA KURIKULUM MERDEKA UNTUK MEMBENTUK PROFIL PELAJAR PANCASILA: STUDI LITERATUR - Lintang Safitri; Maya Susanti; Cindy Anggun; Sri Wahyuni; Firdha Yusmar; Ulin Nuha (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The purpose of this research is to analyze the influence of local wisdom-based science learning in shaping the character of the Pancasila Student Profile. The main characteristics of the independent curriculum are the development of soft skills and the character of students in accordance with the Pancasila Student Profile. One of the essential lessons in the independent curriculum in science learning. Science learning in the independent curriculum aims to develop students’ basic abilities to analyze natural and technological phenomena that appear in everyday life systematically and critically. The development of science learning can be carried out according to regional advantages and uniqueness. The existence of this local wisdom element trains students to be able to scientifically study local wisdom in their surroundings. Planting and growing the value of local wisdom and the character of students can be referenced from learning science. The method in this research is a Literature Study using studies and research based on Google Scholar which consists of 5 articles, documents, and books based on publications in the last 10 years that are relevant to the research topic. The results of the analysis of the five articles show that science learning based on local wisdom can be used as a reference for learning to instill local wisdom values and students' character. So that it can make students who are characterized, competent, and behave in accordance with the values of Pancasila.